The Effect of Grain Size and Density on the Thermoelectric Properties of Bi2Te3-PbTe Compounds - Yoon, Sejin; Kwon, O-Jong; Ahn, Seunghyun; Kim, Jae-Yeol; Koo, Hyun; Bae, Sung-Hwan; Cho, Jun-Young; Kim, Jin-Sang; Park, Chan (SPRINGER, 2013)
The effects of microstructure on thermoelectric properties were investigated in Bi2Te3-PbTe compounds of different grain size and density. Powders of two different sizes [0.1 mu m to 1 mu m (micropowder) and < 50 nm (nanopowder)] were prepared from Bi2Te3-PbTe ingots by ball milling and high-energy ball milling. Three different samples were spark plasma sintered from each powder and the mixture of the two powders. The grain size and relative density of the sintered samples varied from 100 nm to a few micrometers and 89.7% to 97.3%, respectively. The dimensionless figure of merit zT of the sample sintered from nanopowder was about 0.50 at 500 K, being about 3.3 times larger than that of the sample sintered from micropowder (similar to 0.15 at 500 K), when the relative density of the former and the latter were 89.7% and 97.3%, respectively. The improved thermoelectric performance of the samples may originate from the decrease of the thermal conductivity, which was caused by the decrease of the grain size and the increase of the amount of pores.